Embedded research: a promising way to create evidence-informed impact in public health?. (9th March 2018) - Cheetham, M; Wiseman, A; Khazaeli, B; Gibson, E; Gray, P; Van der Graaf, P; Rushmer, R
Abstract: Background: Embedded research (ER) is recognized as one way to strengthen the integration of evidence into public health (PH) practice. In this paper, we outline a promising example of the co-production of research evidence between Fuse, the UKCRC Centre for Translational Research in Public Health and a local authority (LA) in north east England. Methods: We critically examine attempts to share and use research findings to influence decision-making in a LA setting, drawing on insights from PH practitioners, managers, commissioners and academic partners involved in this organizational case study. We highlight what can be achieved as a co-located embedded researcher. Results: The benefits and risks of ER are explored, alongside our reflections on the added value of this approach and the institutional prerequisites necessary for it to work. We argue that while this is not a new methodological approach, its application in PH as a way to facilitate evidence use is novel, and raises pragmatic and theoretical questions about the nature of impact and the extent to which it can be engineered. Conclusion: With increased situated understanding of organizational culture and norms and greater awareness of the socio-political realities of PH, ER enables new co-produced solutions to become possible.